VD_FINDINFO Jug / 2011 / 85 vom 5. Januar 2011 - VD Tribunal cantonal (2011)
CONSTATATION DES FAITS, EXCÈS ET ABUS DU POUVOIR D'APPRÉCIATION, POUVOIR D'APPRÉCIATION | 398 al. 3 let. a CPP (CH), 398 al. 3 let. b CPP (CH)